Design and synthesis of wool-like Co-Mg compound@NiMoO4 nanosheet material for high performance supercapacitors. (April 2018) - Zhang, Yu; Xue, Wei-dong; Yin, Huan; He, Dong-xu; Zhao, Rui
Abstract: We have elaborated nanocomposite electrodes, which were designed and synthesized via facile hydrothermal with further annealing processes of NiMoO4 nanosheets on cobalt and magnesium double hydroxide (DH) growing directly on Ni foam. The integrated electrode (the optimum hydrothermal time 6 h) designed according to this structural pattern, had an excellent electrochemical performance along with a high areal-specific capacitance of 6.50 F cm −2 at 5 mA cm −2 and retained 56% at 60 mA cm −2, the capacitance of the electrode material remained 74% after 5000 cycles at 40 mA cm −2 . The Co-Mg compound@NiMoO4 and activated carbon were assembled into an asymmetric supercapacitor (Co-Mg compound@NiMoO4 //AC), which allowed the feasible voltage could reach 1.6 V and a high energy density of 57 W h kg −1 at the power density of 0.4 kW kg −1 . The Co-Mg compound@NiMoO4 //AC also showed significant cyclic stability with the capacitance retention of 87% after 5000 cycles.